Counselling skills for nurses, midwives, and health visitors - Freshwater, Dawn (Counselling skills., 2003)
"This book is compact and easy to read, and could make a significant contribution to practitioners' ability to communicate effectively and make their practice patient centred."--"Journal of Clinical Nursing". "This is a delightful book which is well written, easy to read and suitable for students, qualified nurses and those who are specialist nurses."--"Journal of Community Nursing". Counselling is a diverse activity and there are an increasing number of people who find themselves using counselling skills, not least those in the caring professions. There is a great deal of scope in using counselling skills to promote health in the everyday encounters that nurses have with their patients. The emphasis on care in the community and empowerment of patients through consumer involvement means that nurses are engaged in providing support and help to people to change behaviours. Community nurses often find themselves in situations which require in-depth listening and responding skills: for example, in helping people come to terms with chronic illness, disability and bereavement.; Midwives are usually the first port of call for those parents who have experienced miscarriages, bereavements, or are coping with decisions involving the potential for genetic abnormalities. Similarly, health visitors are in a valuable position to provide counselling regarding the immunization and health of the young infant. These practitioners are having to cope not only with new and diverse illnesses, for example HIV and AIDS, but also with such policy initiatives as the National Service Framework for Mental Health and their implications. This book examines contemporary developments in nursing and health care in relation to the fundamental philosophy of counselling, the practicalities of counselling and relevant theoretical underpinnings. Whilst the text is predominantly aimed at nurses, midwives and health visitors, it will also be of interest to those professionals allied to medicine, for example physiotherapists, occupational therapists and dieticians